Smart and eco-friendly N-isopropylacrylamide and cellulose hydrogels as a safe dual-drug local cancer therapy approach. (1st November 2022) - Andrade, Fernanda; Roca-Melendres, María Mercé; Llaguno, Monserrat; Hide, Diana; Raurell, Imma; Martell, María; Vijayakumar, Sekar; Oliva, Mireia; Schwartz, Simó; Durán-Lara, Esteban F.; Rafael, Diana; Abasolo, Ibane
Abstract: Local cancer treatment by in situ injections of thermo-responsive hydrogels (HG) offers several advantages over conventional systemic anti-cancer treatments. In this work, a biodegradable and multicompartmental HG composed of N-isopropylacrylamide, cellulose, citric acid, and ceric ammonium nitrate was developed for the controlled release of hydrophilic (doxorubicin) and hydrophobic (niclosamide) drugs. The formulation presented ideal properties regarding thermo-responsiveness, rheological behavior, drug release profile, biocompatibility, and biological activity in colon and ovarian cancer cells. Cellulose was found to retard drugs release rate, being only 4 % of doxorubicin and 30 % of niclosamide released after 1 week. This low release was sufficient to cause cell death in both cell lines. Moreover, HG demonstrated a proper injectability, in situ prevalence, and safety profile in vivo . Overall, the HG properties, together with its natural and eco-friendly composition, create a safe and efficient platform for the local treatment of non-resectable tumors or tumors requiring pre-surgical adjuvant therapy. Graphical abstract: Unlabelled Image